Effect of fertilization on rhizome and starch yield of achira (Canna edulis, Ker) in Nariño, Colombia - Volveras-Mambuscay, Belisario (2022)
Introduction. In Colombia, achira (Canna edulis, Ker) starch production is important in the Andean zone, in the departments of Nariño, Huila, and Cundinamarca. Objective. To evaluate the effect of planting density and fertilization on achira starch and rhizome yield, and the relationship between them, in the department of Nariño, Colombia. Materials and methods. Between September 2016 and October 2017 trials were installed in two locations in the municipality of La Cruz Nariño, Colombia. With BCA design distributed in sub-sub-divided plots with the following treatments: the blocks were composed of two main plots corresponding to two regional cultivars of achira, the sub-plots corresponded to two planting densities 10,000 and 12,500 plants/ha and the sub-sub-plots corresponded to three levels of N, P2O5, and K2O with chemical source and organic fertilizer. Results. The rhizome yield was higher than the national average with all treatments; the best yield was obtained at the highest level of chemical fertilization. There was a better response of the purple cultivar with 6.15 t ha-1 of starch, 15 % more than the green cultivar and a 21 % higher starch/rhizome yield. With the highest planting density, 15 % more starch was obtained, and with organic fertilizer the starch yield was higher than the regional average, but 50 % lower than with chemical fertilization, with which an average of 6.23 t ha-1 was obtained. Conclusion. There was a response of the achira to the N-P-K application and the planting density on achira starch and rhizome yield, and the relationship between both, in addition a different agronomic response of the cultivars under the study conditions was found.